Review of Daniel Leech-Wilkinson. 2002. The Modern Invention of Medieval Music: Scholarship, Ideology, Performance. Cambridge: Cambridge University Press - Irvine, Thomas (Current Musicology, 2004)
Anyone who has heard medieval music in live performance or on record in the last fifty years knows the sound that medieval music used to make: the joyful yowling of a mixed crew of instrumentalists, bowing, tooting, honking, and plucking, and-in the best performances-above it all, a single, ecstatic voice. Anyone who has listened to such music in the last twenty knows the sound it tends to make now: a blended and-again, in the best renditions- no-Iess-ecstatic combination of purely intoned a cappella voices. The former is now widely regarded to be “unhistorical”; it is a model that has been “superseded;’ thanks to “progress” in historical research. The Modern Invention of Medieval Music tells the story of how a music changed its sound because scholars re-thought its history and how a music changed its history because musicians re-thought its sound.